A Short Version of the EFECO Online Questionnaire for the Assessment of Executive Functions in School-Age Children - Sabina Barrios-Fernandez; Margarita Gozalo; Maria Amado-Fuentes; Jorge Carlos-Vivas; Andres Garcia-Gomez (MDPI AG, 2021)
Executive function (EF) is a group of processes that allow individuals to be goal-oriented and to have adaptive functioning, so that adequate performance is essential for success in activities of daily living, at school and in other activities. The present study aims to create a short version of the Executive Functioning Questionnaire (EFECO) since there is a gap in the Spanish literature due to the lack of behavioural observation questionnaires at school age. A total of 3926 participants completed the online questionnaire. Subsequently, the validity and reliability of the data are analysed. The results show that the short version of the questionnaire, the EFECO-S, has a structure with five dimensions (emotional self-control, initiation, working memory, inhibition, and spatial organisation), as well as a second-order factor (global executive skill) and high reliability (ordinal Alpha = 0.68-0.88). The EFECO is composed of 67 items, while the EFECO-S has 20 items, four per factor, which turns it into a quick and easy to apply test. Therefore, it becomes an interesting alternative to be applied in screening processes with children who may be experiencing executive difficulties.